The Development of autobiographical memory. [article]. - Fivush, Robyn
Autobiographical memory is a uniquely human system that integrates memories of past experiences into an overarching life narrative. In this review, I exctend social-cultural models of autobiographical memory development and present theory and research that demonstrates that a) autobiographical memory is a gradually developing system across childhood and adolescence that depends on the development of a sense of sufjective self as continuous in time; b) autobiographical memory develops within specific soical and cultural contexts that related to individual, gendered, and cultural differences in adults' autobiographical memories, and, more specifically. c) mothers who reminisce with their young children elaborated and evaluative wayhs have children who develop more detailed, coherent, and evaluative autobiographical memories. - (from the author)
Keywords: Episodic memory; Social-cultural theory; Life narrative; Maternal reminiscing style; Subjective self